Strategi Reseller dalam Meningkatkan Penjualan Produk Pengkilap Mobil/Motor yang Diproduksi oleh Inkubator Bisnis Graphene Guard di Universitas Riau - Amri, Amun; Reni Yenti, Silvia; Heltina, Desi; Herman, Syamsu; Aziz, Azridjal; Nadhifah, Evi; Ekwarso, Hendro (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Efforts to increase sales of car/motorcycle polish products have been carried out by the Graphene Guard business incubator. This product is a downstream research result of lecturer/researcher at the Faculty of Engineering, Riau University. As a new product and not yet known to the public, special strategies are needed to increase sales. In the initial stage, an online and offline sales strategy was carried out, but apparently it did not show encouraging results even though promotions had been carried out. It was felt that a reseller strategy needed to be implemented. The reseller strategy, especially offline resellers, was addressed to the students at Riau University with attractive prices and bonuses. This strategy generated significant sales in a relatively short time. The phenomenon where offline reseller sales results were very different from conventional sales strategies reflecting the changes in consumer behavior and increasingly complex market dynamics. Reseller marketing strategies, especially when carried out by individuals or small groups, often conveyed a strong sense of personalization and trust. In this strategy, focus was given to product advantages, customer testimonials, and real interactions. This created high levels of trust in consumers, and allowed them to feel confident in purchasing the product. This strategy can be a valuable experience for marketing of new products.